2014
DOI: 10.1002/chem.201402433
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Scope and Mechanism of Nickel‐Catalyzed Transformations of Glycosyl Trichloroacetimidates to Glycosyl Trichloroacetamides and Subsequent, Atom‐Economical, One‐Step Conversion to α‐Urea‐Glycosides

Abstract: The development and mechanistic investigation of a highly stereoselective methodology for preparing α-linked-urea neo-glycoconjugates and pseudo-oligosaccharides is described. This two-step procedure begins with the selective nickel-catalyzed conversion of glycosyl trichloroacetimidates to the corresponding α-trichloroacetamides. The α-selective nature of the conversion is controlled with a cationic nickel(II) catalyst, Ni(dppe)(OTf)2. Mechanistic studies have identified the coordination of the nickel catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 111 publications
0
10
0
Order By: Relevance
“…On the other hand, use of 10 mol% Ni(4-F-PhCN) 4 (OTf) 2 catalyst (entry 3) improved the yield of the product 8 (17%→ 30%), but undesired [1,3]-rearrangement trichloroacetamide was still observed in the coupling event. 31 In order to prevent the trichloroacetamide byproduct, donor 4 , N- phenyltriflouroacetimidate, 32 was employed (entries 4 and 5). When Ni(4-F-PhCN) 4 (OTf) 2 was utilized and the coupling reaction was heated to 35°C, a significant improvement in formation of the desired disaccharide 8 (58%, entry 5) was observed.…”
mentioning
confidence: 99%
“…On the other hand, use of 10 mol% Ni(4-F-PhCN) 4 (OTf) 2 catalyst (entry 3) improved the yield of the product 8 (17%→ 30%), but undesired [1,3]-rearrangement trichloroacetamide was still observed in the coupling event. 31 In order to prevent the trichloroacetamide byproduct, donor 4 , N- phenyltriflouroacetimidate, 32 was employed (entries 4 and 5). When Ni(4-F-PhCN) 4 (OTf) 2 was utilized and the coupling reaction was heated to 35°C, a significant improvement in formation of the desired disaccharide 8 (58%, entry 5) was observed.…”
mentioning
confidence: 99%
“…NMR spectra were recorded in CDCl 3 , with residual chloroform or TMS used as the internal reference. The trichloroacetimidates 1 , 25 3 , 26 11 , 27 17 , 15e 21 , 15e 25 , 28 27 , 29 29 , 30 37 , 15e 45 , 17 47 , 11b,31 and 49 32 were prepared as previously described, while tert -butyl 2,2,2-trichloroacetimidate 43 and ethyl 2,2,2-trichloroacetimidate 51 were purchased from commercial sources and used without further purification. The synthesis and analysis of the enantiopurity of the chiral trichloroacetimidate ( S )-3 was performed as previously reported.…”
Section: Methodsmentioning
confidence: 99%
“…More recently Motawia and co-workers described conditions for promoting the rearrangement of glycosyl trichloro­acetimidates to glycosyl trichloroacetamides utilizing catalytic TMSOTf . Nguyen and co-workers have also developed a transition-metal-catalyzed rearrangement of glycosyl trichloro­acetimidates to the corresponding acetamides, which are utilized in the synthesis of glycosyl ureas . Some specific trichloro­acetimidate systems (such as α-methylene-β-trichloro­acetimidate alkanoates, α-diazo-β-trichloro­acetimidate carbonyl compounds, and “doubly activated” imidates, being both benzylic and propargylic) rapidly rearrange to the trichloro­acetamide, which may preclude isolation of the imidate.…”
mentioning
confidence: 99%
“…During these studies it was confirmed that the β-TCA donor was unreactive toward the Ni­(II) catalyst as previously reported, whereas only the α-TCA donor facilitated the formation of a glycoside with excellent α-selectivity. Ni catalysts were also reported by the Nguyen group to catalyze the formation of trichloroacetamide from TCA donors in order to obtain N -glycosides with high α-selectivity …”
Section: Glycosyl Imidate Donorsmentioning
confidence: 97%